Endoscopic Identification of the Pharyngeal (Palatovaginal) Canal: An Overlooked Area - Herzallah, Islam R.; Amin, Sameh; El-Hariri, Mona A.; Casiano, Roy R. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective The pharyngeal or palatovaginal canal (PC) is a small tunnel that lies between the sphenoid process of the palatine bone and the vaginal process of the sphenoid bone. Currently, little endoscopic information is available about this region.Design and Setting Endoscopic endonasal cadaveric study.Subjects and Methods Twenty sides in 10 adult cadaver heads were studied endoscopically. The sphenopalatine foramen (SPF) and the adjacent pterygopalatine fossa were exposed. Dissection medial to the vidian canal demonstrated a tunnel that runs posteromedially in the sphenoid floor. Endoscopic data were documented. Additionally, canal measurements were obtained on 20 sides from coronal CT scans of paranasal sinuses.Results The PC was identifiable in 85% of the sides, although thickness of its bony wall was variable. The endoscopic relationship of the canal and its artery with other landmarks is described. Radiologically, the diameter of the PC averaged 1.7 mm, and the mean distance from the PC to the vidian canal was 3.78 mm.Conclusion The current study provides a novel endoscopic identification of an overlooked canal. The pharyngeal artery can be a source of bleeding during extended endoscopic procedures. The PC itself could be a place for finger-like projections of anatomically related neoplasms.
Keywords: pharyngeal canal; palatovaginal canal; pharyngeal artery; pterygopalatine fossa; sphenopalatine foramen; vidian canal; epistaxis; endoscopic sinus surgery